Analisis Pengaruh Atribut Iklan Televisi terhadap Ekuitas Merek - Muhamad Ali Sukrajap (Jurnal Maksipreneur, 2013)
The corporate world has level changes very quickly. It is no wonder that the producers are vying to sell their products in order to quickly sell at the market. Frequently used media channels are through advertising. One of the kind advertising are television commercials. The making of television advertising must be pleasing consumers, meaning that in designing the ads need to pay attention to the ad attribute in order to make consumers interested in finding out more about the product and brand preference of the planting efforts in the minds consumers. Television advertising is one way to manage a good brand equity. This study aims to measure the extent of the influence of television advertising in the attribute of ad Sprite version "Speed" affecting equity product brand of Sprite. The data used in this research in the form of primary data taken directly from the data source through the survey with the total number of respondents (n) of 100 respondents. All data processed by using Structural Equation Model analysis tools in LISREL 8.54. From the results of the study, the researchers concluded that, in general there are positive influence of the television commercials attributes against the brand equity of the product but if we break into one on one relationship there are some specifically outlined the ads have no effect positively towards brand equity i.e. the animation and color while the ad attributes the most positive influence is the tagline.